2019
DOI: 10.1002/rmb2.12281
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of chromosomal abnormalities in patients with recurrent pregnancy loss, focusing on the prognosis of patients with inversion of chromosome (9)

Abstract: Purpose Inversion of chromosome 9 (inv[9]) is considered to be a normal variant, and the inv(9) in patients or husbands with recurrent pregnancy loss (RPL) is believed to be harmless. However, there are few reports concerning the outcomes of pregnancy in patients with RPL when the patient or their partner has inv(9). In this study, we analyzed the outcomes of pregnancy in this patient population. Methods Chromosomal karyotyping was performed for 2006 couples with RPL (two or more consecutive early pregnancy lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, some chromosomal inversions such as inversion 9 have not been associated with any health problem or RPL 16 . 1qh+, 9qh+, 16qh+,13ps+, 13pstk+ and 22ps+ considered as normal chromosome variants are benign chromosome variants which are not associated with any health problem.…”
Section: Resultsmentioning
confidence: 99%
“…However, some chromosomal inversions such as inversion 9 have not been associated with any health problem or RPL 16 . 1qh+, 9qh+, 16qh+,13ps+, 13pstk+ and 22ps+ considered as normal chromosome variants are benign chromosome variants which are not associated with any health problem.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, Dana et al [22] showed no statistical difference between the rates of the inversion 9 variant in male vs. female carriers with a history of infertility ( p = 0.343). Nonaka et al [23] also showed no statistical difference between the rates of the inversion 9 variant in male vs. female carriers with a history of recurrent pregnancy loss ( p = 0.175). Furthermore, both Dana et al [22] and Kosyakova et al [24] reported no evidence for a correlation between the inversion 9 variant and infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both Dana et al [22] and Kosyakova et al [24] reported no evidence for a correlation between the inversion 9 variant and infertility. Similarly, Nonaka et al [23] studied the pregnancy outcomes in couples with recurrent pregnancy loss where one partner carried an inversion 9 variant and reported that this chromosome finding has no adverse implication on subsequent pregnancies. Karyotyping on villi from products of conception samples from these patients also did not identify any miscarriages with an unbalanced form of the inversion.…”
Section: Discussionmentioning
confidence: 99%
“…CIN can lead also to infertility affecting the mitotic self-renewing cells from the germ line, that ultimately give rise the gametes. One example is the inversion of chromosome 9 in human, present in 2.6% of the population and it is associated to recurrent pregnancy loss [197].…”
Section: Fertilitymentioning
confidence: 99%